2012
DOI: 10.1128/jvi.00437-12
|View full text |Cite
|
Sign up to set email alerts
|

Initial HIV-1 Antigen-Specific CD8 + T Cells in Acute HIV-1 Infection Inhibit Transmitted/Founder Virus Replication

Abstract: mediated virus inhibition than cognate T/F viruses, demonstrating that the virus escapes early from CD8؉ T cell-mediated inhibition of virus replication. CD8 ؉ T cell antigen-specific subsets mediated inhibition of T/F virus replication via soluble components, and these soluble responses were stimulated by peptide pools that include epitopes that were shown to drive HIV-1 escape during AHI. These data provide insights into the mechanisms of CD8-mediated virus inhibition and suggest that functional analyses wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 60 publications
5
69
1
Order By: Relevance
“…This is in line with results obtained for EC and chronic subjects with broad anti-Gag responses (16,35) and could provide an additional mechanistic explanation for the pivotal role of Gag-specific cells in delayed disease progression. Although Freel et al (41) found that Nefspecific cells could mediate VIA to the same extent as Gag-specific cells in acutely infected subjects, no association between these activities and clinical parameters was studied by these authors, as it is the case of the present work. Also, it is important to denote that both studies differ in definition of the specificity of VIA-mediating cells, which may account for the different results obtained.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…This is in line with results obtained for EC and chronic subjects with broad anti-Gag responses (16,35) and could provide an additional mechanistic explanation for the pivotal role of Gag-specific cells in delayed disease progression. Although Freel et al (41) found that Nefspecific cells could mediate VIA to the same extent as Gag-specific cells in acutely infected subjects, no association between these activities and clinical parameters was studied by these authors, as it is the case of the present work. Also, it is important to denote that both studies differ in definition of the specificity of VIA-mediating cells, which may account for the different results obtained.…”
Section: Discussioncontrasting
confidence: 52%
“…4). To our knowledge, there exists only one very recent report studying VIA in acute HIV infection (41). In that work, Freel and collaborators also demonstrate (i) that VIA magnitude correlates with the percentage of HIV-specific CD8 ϩ T cells expressing CD107A, MIP-1␤, and IFN-␥ and with the secretion of MIP-1␣, MIP-1␤, IFN-␥, IP-10, and IL-1␣ after cell stimulation with peptide antigens and (ii) that early escape from CD8 ϩ T-cell-mediated VIA occurs during PHI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, several recent studies have highlighted the importance of the virus inhibition assays which is a new assay measuring CD8 + T-cell mediated inhibition of virus replication in vitro [35][36][37][38]. This assay may be relevant as it directly reflects the ability of virus-specific CD8 + T cells to limit HIV spreading and does thus integrate several components of the immune response such as the effector function and the recognition of distinct virus isolates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the initial antigen-specific CTL response to T/F viruses contributes to the control of acute viremia in infected individuals (46,47). How T/F viruses interact with MDDCs and induce antigen presentation is not fully characterized.…”
Section: Discussionmentioning
confidence: 99%